Congenital heart disease. The national society journals present selected research that has driven recent advances in clinical cardiology. Issue 21 (2nd September 2012) - Burch, Michael; Dedieu, Nathalie
Abstract : This Almanac highlights recent papers on congenital heart disease in the major cardiac journals. Over 100 articles are cited. Subheadings are used to group relevant papers and allow readers to focus on their areas of interest, but are not meant to be comprehensive for all aspects of congenital cardiac disease.